Nature-derived otolith loaded polyethylene glycol-polycaprolactone electrospun composite nanofiber membranes: preparation, characterization, and biocompatibility evaluation - Pekdemir, Sibel Selcuk; Gedik, Kubra Karadas; Kurucay, Ali; Onay, Hatice; Ulu, Ahmet; Pekdemir, Mustafa Ersin; Ates, Burhan (Springer, 2025)
The electrospun nanofibers have paid much attention to biomedical applications. In this study, the electrospun composite nanofibers were prepared based on optimized polycaprolactone (PCL, 12 wt%) and polyethylene glycol (PEG, 3.6 wt%) polymers loaded with otoliths particles (OTO, 10-30 wt%) by electrospinning technique. The morphological, molecular interactions, crystallinity, and thermal properties of the composite nanofiber membranes were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and differential scanning calorimetry. In addition to that, swelling behaviors, biodegradability, porosity, and biocompatibility were also evaluated. Both PEG/PCL and OTO/PEG/PCL nanofibers revealed bead-less constructions with average diameters of around 500 nm. Thermogravimetric analysis revealed OTO/PEG/PCL composite membranes thermally stable up to 300 degrees C. XRD results also indicated a good crystallinity for the OTO/PEG/PCL composite membranes due to higher crystallinity of otolith. Adding otolith to PEG/PCL nanofibers did not obviously change the water uptake capacity, biodegradability, and porosity while increasing swelling ratio. Finally, membranes with the lowest otolith concentration (10% w/w) showed 96.2% cell viability, while increasing otolith concentration decreased cell viability. Based on the obtained results, the cytotoxicity of OTO/PEG/PCL membranes was evaluated with mouse fibroblast (L-929) cells by more than 85% survival during 72 h, which revealed that the OTO/PEG/PCL membranes were non-toxic. Taken together, these data suggest that OTO/PEG/PCL membranes could potentially be used as a nanofiber scaffold for applications.
Keywords: Otolith; Polycaprolactone; Polyethylene glycol; Electrospun composite nanofiber; Biocompatibility